Safety Systems for Working with Pesticides - Frederick M. Fishel (EDIS, 2008)
PI-168, a 3-page illustrated fact sheet by Frederick Fishel, provides a description of the following pesticide safety systems: closed mixing and loading systems, enclosed cabs, and containment systems. Published by the UF Department of Agronomy, August 2008.